2021
DOI: 10.3389/fbioe.2021.666121
|View full text |Cite
|
Sign up to set email alerts
|

Advanced DNA Detection via Multispectral Plasmonic Metasurfaces

Abstract: We propose and demonstrate a sensing platform based on plasmonic metasurfaces for the detection of very low concentrations of deoxyribo-nucleic acid (DNA) fragments. The platform relies on surface-enhanced infrared absorption spectroscopy, implemented via a multispectral metasurface. Specifically, different regions (“pixels”) are engineered so as to separately cover the medium-infrared range of the electromagnetic spectrum extending from the functional-groups to the fingerprint region of a single analyte. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The basic geometry is schematized in Figure 1 a,b: we consider cross-shaped gold NAs (of thickness t = 50 nm, arm length L , and arm width W ) arranged on a 2-D periodic square grid (of period P ), laid on a silicon substrate, embedded in air. Such geometry has already been successfully utilized in previous studies [ 37 , 38 , 39 ], demonstrating very good performance in terms of field enhancement and robustness with respect to polarization. Assuming, for simplicity, infinite periodicity in the transverse plane and normally incident plane-wave illumination from the air region, we can reduce our study to a single 3-D unit-cell (shown in Figure 1 a), with the lateral walls terminated with periodic boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The basic geometry is schematized in Figure 1 a,b: we consider cross-shaped gold NAs (of thickness t = 50 nm, arm length L , and arm width W ) arranged on a 2-D periodic square grid (of period P ), laid on a silicon substrate, embedded in air. Such geometry has already been successfully utilized in previous studies [ 37 , 38 , 39 ], demonstrating very good performance in terms of field enhancement and robustness with respect to polarization. Assuming, for simplicity, infinite periodicity in the transverse plane and normally incident plane-wave illumination from the air region, we can reduce our study to a single 3-D unit-cell (shown in Figure 1 a), with the lateral walls terminated with periodic boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In a series of ongoing studies [ 37 , 38 , 39 ], we have focused on the optimized design and fabrication of plasmonic MSs for SEIRA spectroscopy. For the design, we have developed some accurate and effective forward- and inverse-modeling strategies for selecting the NA shape and spatial arrangement, aimed at maximizing the detection sensitivity even for extremely small molecules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these transduction mechanisms are based on the localized surface plasmon resonance (LSPR) exhibited by noble‐metal NPs. [ 20,21 ] Refractometric biosensors exploit the LSPR shifts as a function of a target analyte when properly interacting with the biorecognition element adhered on the surface of the NPs; [ 22,23 ] Surface‐enhanced infrared absorption (SEIRA) and surface‐enhanced raman scattering (SERS) exploit the LSPR to enhance infrared and Raman signals of molecules onto plasmonic substrates; [ 24–26 ] Metal‐enhanced fluorescence (MEF), also referred to as plasmon‐enhanced fluorescence (PEF), exploit the LSPR to increase the signal intensity of fluorescent dyes, depending on the spectral overlapping between plasmonic absorption and fluorescent dye extinction/emission and their separation distance. [ 27–30 ] Moreover, the combination of plasmonic nanoparticles with polymers has been enabling novel functionalities and transduction mechanisms based on the different mechanical properties of flexible substrates.…”
Section: Introductionmentioning
confidence: 99%